Ki Hadjar Dewantara and the Philosophy of Education - Diyoba Azhar Fuadi; Gusti Yuniarti; Nelian Nelesti; Septen Heri; Jon Carnolis; Merri Sri Hartati; Susiyanto Susiyanto (Indonesian Journal of Innovation Multidisipliner Research, 2025)
Education has a major role in building a strong country and producing talented citizens. However, the Indonesian education system still places too much emphasis on academic aspects rather than character and moral development. Ki Hadjar Dewantara's ideas, which emphasize building national character, remain relevant in this era of globalization. This research uses a literature study method by analyzing various literature related to Ki Hadjar Dewantara's thoughts, educational philosophy, and current educational challenges. Data was obtained from books, journals and Ki Hadjar Dewantara's writings which document his views on education and culture. The research results show that Ki Hadjar Dewantara's educational concept is based on the principle "Ing ngarso sung tulodo, ing madyo mangun karso, tut wuri handayani" which emphasizes the importance of example, motivation and guidance in education. Apart from that, his thinking is also related to various schools of educational philosophy, such as essentialism, existentialism, progressivism and perennialism. In conclusion, Ki Hadjar Dewantara's thoughts provide a strong philosophical foundation for the Indonesian education system in facing changing times. The integration of national values, culture and morality in education can be a solution to create a generation that is intelligent, has character and has a high sense of social responsibility.